Impact of Education on Adolescent Girls' Ability to Perform Early Detection of Breast Cancer as an Effort to Face Pre-Health Crisis (International Forum of Researchers and Lecturers, 2025)
Breast cancer remains a major contributor to female mortality in Indonesia. One effective method to enhance survival rates and avoid delayed diagnosis is early detection through breast self-examination (BSE). Despite this, the level of awareness and understanding of BSE among adolescent girls is still insufficient. This study aimed to evaluate the impact of an educational intervention on improving the knowledge and practical skills of female adolescents in conducting BSE as a preventive approach to avoid potential health crises. A pre-experimental research design was used, employing a one-group pre-test and post-test approach. The participants consisted of 50 eleventh-grade female students from SMK Negeri 4 Makassar, selected through purposive sampling techniques. The educational program was delivered through lectures, interactive discussions, and practical demonstrations. Data collection instruments included a structured knowledge questionnaire and a checklist to assess BSE practice. Results revealed a notable increase in the average knowledge score, rising from 5.86 before the intervention to 8.78 afterward. Similarly, the average score for BSE practice improved from 3.74 to 7.62. Statistical analysis using the Wilcoxon test produced a p-value of 0.000, signifying that the educational intervention had a significant positive effect on students’ ability to recognize early signs of breast cancer. The findings suggest that targeted health education can significantly enhance both awareness and self-examination skills among adolescent girls. Therefore, integrating BSE education into school health programs is strongly recommended to foster preventive behaviors and empower young women to monitor their own breast health proactively. It is recommended that BSE education be included as a regular program in schools as part of preventive health promotion.